Diuretika-Therapie - Büttner, Stefan; Koch, Alexander; Pfeilschifter, Josef (DMW - Deutsche Medizinische Wochenschrift, 2019)
The treatment of generalized edema includes primarily the treatment of the underlying disease as well as the sodium restriction. Often, however, the volume balance alone can not be controlled satisfactorily. Commonly, diuretics are used for the treatment of chronic heart failure, liver cirrhosis, nephrotic syndrome and renal failure. Diuretics are well documented effective and necessary drugs for the treatment of hypervolemia. From a symptomatic point of view, they are indispensable for cardiac decompensation and they have a firm place in the treatment of hypertension. Due to the different effects as well as pharmacological differences, diuretics can be used for differential therapeutics. The therapy can be associated with side effects. Sequential nephron blockade may be useful in diuretic resistance, but evidence in controlled trials is still lacking. This review provides an overview of the mechanisms, diuretic use and diuretic resistance.
Keywords: Schleifendiuretika; Thiazide; Ödeme; Natriumrestriktion; Diuretika-Resistenz